2013
DOI: 10.1093/jxb/ert402
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms involved in plant adaptation to low K+ availability

Abstract: Potassium is a major inorganic constituent of the living cell and the most abundant cation in the cytosol. It plays a role in various functions at the cell level, such as electrical neutralization of anionic charges, protein synthesis, long- and short-term control of membrane polarization, and regulation of the osmotic potential. Through the latter function, K(+) is involved at the whole-plant level in osmotically driven functions such as cell movements, regulation of stomatal aperture, or phloem transport. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
105
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 119 publications
(216 reference statements)
3
105
0
Order By: Relevance
“…A similar influence of K availability on crop productivity under rain-fed conditions was found for banana production in Uganda (Taulya 2013). The positive effect of K on WUE could be associated with the ability of K to regulate stomatal aperture and closure (Chérel et al 2014), given the high sensitivity of cassava to leaf-to-air vapour pressure deficit. This mechanism allows the crop to consume the limited amount of available water slowly during the dry season, resulting in greater dry matter gain over the stress period and larger WUE over the cropping season (El-Sharkawy 2004).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…A similar influence of K availability on crop productivity under rain-fed conditions was found for banana production in Uganda (Taulya 2013). The positive effect of K on WUE could be associated with the ability of K to regulate stomatal aperture and closure (Chérel et al 2014), given the high sensitivity of cassava to leaf-to-air vapour pressure deficit. This mechanism allows the crop to consume the limited amount of available water slowly during the dry season, resulting in greater dry matter gain over the stress period and larger WUE over the cropping season (El-Sharkawy 2004).…”
Section: Discussionsupporting
confidence: 55%
“…Potassium applications increased RUE, storage roots and total biomass production in Djakakope, but did not significantly affect IPAR. The reported beneficial effects of K on plant growth include CO 2 assimilation for photosynthesis, enzyme activation or stimulation and protein synthesis (Chérel et al 2014). Potassium application increases leaf K + concentration, especially cytosolic K + and chloroplast K + , which enhances the photosynthetic rate of a specific leaf area (Marschner and Marschner 1995 , resulting in decreased photosynthesis, which can be overcome through external K supply (Marschner and Marschner 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, K + content in living cells were maintained at a higher level, and Na + toxic effect in the cytoplasm was somewhat avoided. In terms of Na + influx and K + efflux from vacuoles, some studies reported that over-expression of tonoplast sodium/proton exchangers (NHXs) improved salt tolerance in Beta vulgaris (Blumwald and Poole, 1987;Xia et al, 2002;Adler et al, 2010), and tonoplast-located K + channels or transporters facilitating K + release from vacuoles into the cytoplasm (Wang and Wu, 2010;Chérel et al, 2014). The ability of Swiss chard to control the cytoplasmic K + concentration in Alkalinity+2 mM K and Alkalinity+0 mM K conditions could possibly have been regulated by the over-expression of NHXs or tonoplast-located K + channels and transporters, however, these phenomena need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the osmotic adjustment was retorted; the contents of K , and the activities of catalase, guaiacol peroxidase, and glutathione reductase were increased. On other hand, K + supplementation in sodic-alkaline conditions helped to maintain guaiacol peroxidase activity similar to that of control plants, and reduced malondialdehyde content when compared with plants treated in sodic-alkaline conditions without K Introduction Potassium (K + ) is major inorganic constituent of living cells and required in large amounts for plant growth and development, being taken from soil then translocated to various organs for many processes in plant cells (Kanai et al, 2011;Chérel et al, 2014). Plants need a high content of K + for specific functions in the cytoplasm and 90% is localized in vacuoles (Wakeel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%